1995
DOI: 10.1080/07315724.1995.10718516
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and oxidant stress: nutritional, environmental, and genetic risk factors.

Abstract: A considerable body of evidence suggests that oxidant stress results in inflammation and tissue damage in the respiratory system, and later in immune damage, and that individuals with lowered cellular reducing capacity are at increased risk to develop asthma. Reducing capacity in the erythrocyte is generated through the pentose phosphate pathway and this pathway also generates a major portion of the reducing capacity in all cells of the body. Therefore, dietary, environmental, and genetic factors which diminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 47 publications
0
53
1
Order By: Relevance
“…The initial proposal of Seaton et al (1994) has been examined in a case-control study (Soutar et al 1997) in which it was found that those individuals with the lowest intakes of vitamin C and Mn are associated with a > 5-fold increased risk of bronchial reactivity (Table 3). The various nutrients that have been shown in subsequent casecontrol or cross-sectional studies to be associated with a reduced risk of asthma are vitamins A, C and E, flavones and flavonoids, Mg, Ca, Na, K, Se, Cu, Zn and fatty acids (Schwartz & Weiss, 1990;Greene, 1995;Bodner et al 1999;Smit et al 1999;Fogarty & Britton, 2000;Grievink et al 2000a;Hijazi et al 2000;Romieu & Trenga, 2001;Smit, 2001). However, longitudinal studies have shown that only vitamin E has a protective effect (Troisi et al 1995).…”
Section: Asthmamentioning
confidence: 99%
“…The initial proposal of Seaton et al (1994) has been examined in a case-control study (Soutar et al 1997) in which it was found that those individuals with the lowest intakes of vitamin C and Mn are associated with a > 5-fold increased risk of bronchial reactivity (Table 3). The various nutrients that have been shown in subsequent casecontrol or cross-sectional studies to be associated with a reduced risk of asthma are vitamins A, C and E, flavones and flavonoids, Mg, Ca, Na, K, Se, Cu, Zn and fatty acids (Schwartz & Weiss, 1990;Greene, 1995;Bodner et al 1999;Smit et al 1999;Fogarty & Britton, 2000;Grievink et al 2000a;Hijazi et al 2000;Romieu & Trenga, 2001;Smit, 2001). However, longitudinal studies have shown that only vitamin E has a protective effect (Troisi et al 1995).…”
Section: Asthmamentioning
confidence: 99%
“…In bronchial asthma, various mediators induce the infiltration of mast cells, eosinophils and Th2 lymphocytes into lesions with downstream mediators, resulting in classical asthmatic phenotypes, such as mucous over-production, airway hyper-responsiveness, and submucosal thickness (4).…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance between ROS and antioxidant defenses is defined as oxidative stress, and is involved in relevant processes such as ageing and several degenerative diseases 26 . Free radicals can damage DNA, proteins and lipid membranes.…”
Section: Health Benefits Of Astaxanthinmentioning
confidence: 99%